THE SPACE OF CONTINUOUS FUNCTIONS WITH 2-NORMS - Shelvi Ekariani; MOCHAMMAD IDRIS; DODY ICHWANA PUTRA (Departemen Matematika dan Sains Data FMIPA Universitas Andalas Padang, 2026)
The purpose of this paper is to study the space of continuous functions, C[a,b] as a 2-normed space. In particular, we show that the space is complete with respect to some linearly independent set.